From Structure to Strategy: How Organization Design Influences Innovation and Performance in Micro, Small, and Medium Enterprises (MSMEs) - Dewi, Maya Sari; Ghalib, Saladin; Said, Laila Refiana; Sopiana, Yunita (Journal of Ecohumanism, 2025)
The objective of this study is to investigate relationship between organizational structure, innovation and performance in Micro, Small, and Medium Enterprises (MSMEs), with a particular focus on the mediating role of innovation. The research provides a novel lens by examining how distinct dimensions of organizational structure—formalization, flexibility, centralization, complexity, and specialization—interact with stages of innovation to influence multidimensional performance outcomes. This research explores how structural design aligns with environmental contingencies and drives innovation as a dynamic capability in MSMEs. The integration of these theories enables a nuanced understanding of organizational adaptability and performance within resource-constrained settings.The methodology adopted for this research comprises employing a quantitative cross-sectional design, data from 400 MSMEs was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that innovation significantly mediates the relationship between organizational structure and performance. Key structural dimensions such as flexibility and complexity demonstrate a pronounced impact on adaptive capacity and strategic agility in MSMEs. By integrating structural and innovation paradigms, this study provides actionable insights for policymakers and MSMEs leaders who aim to enhance competitiveness and sustainability in a rapidly evolving business landscape. This research adopts a holistic approach by considering the interactive effects of structural dimensions and staged innovation processes on MSMEs performance. This comprehensive perspective addresses critical gaps in understanding how structural design facilitates continuous innovation and sustainable performance